PENGARUH CITRA MEREK, KUALITAS PRODUK, DESAIN PRODUK, DAN PERSEPSI HARGA TERHADAP MINAT BELI KONSUMEN PADA PRODUK MEREK VICIOUS COLONY DI WEREHOUSE STORE, BANJARMASIN - Tio, Paulus Ryan; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
Creative industries are increasing in Indonesia, one of which is clothing, through the creative industry developed so that the current clothing apparel is not just a mere basic needs but also a lifestyle, through the clothes they wore one can show his true identity and appear more confident. One trend clothing that is currently happening a lot is clothes which sold in distro or distribution outlet where a lot of brands are popping up with a fresh concept and its market share on average are youngster.            The purpose of this study was to determine the effect of brand image, product quality, product design, and the perception of prices on consumer buying interest. The population in this study are all the people who buy the products of Vicious Colony in Werehouse Store, Banjarmasin. The sample in this study was 100 people who buy the products of Vicious Colony in Werehouse Store, Banjarmasin taken by purposive sampling. Data collection is done by using a questionnaire.            t test results prove that all independent variables (brand image, product quality, product design, and price perception) have a positive effect on the dependent variable consumer buying interest of Vicious Colony product in Werehouse Store, Banjarmasin. According to the consumer, the four variables considered important when buying a product of Vicious Colony in Werehouse Store, Banjarmasin. And of the coefficient of determination (adjusted ) obtained at 0,788. This means that 78.8% of buying interest from Vicious Colony product in Werehouse Store, Banjarmasin can be explained by the variable of brand image, product quality, product design, and price perception, while the remaining 21.2% of buying interest are influenced by other variables not examined in this study.